Selective magnetization transfer ratio decrease in the visual cortex following optic neuritis - Audoin, Bertrand; Fernando, Kryshani T M; Swanton, Josephine K; Thompson, Alan J; Plant, Gordon T; Miller, David H (Brain (London, England : 1878), 2006)
Patients with clinically isolated syndromes suggestive of multiple sclerosis have evidence for abnormality in normal appearing grey matter detected using the magnetization transfer ratio (MTR), a quantitative MRI measure. One potential mechanism for the decreased grey matter MTR (GM MTR) observed is trans-synaptic morphological abnormality secondary to demyelinating lesions that are in an anatomically linked pathway but remote location. We investigated this potential association by studying the location of abnormalities using voxel-based analysis of GM MTR maps in a group of 80 patients studied within 6 months of presenting with isolated optic neuritis and compared the findings with those seen in 50 age- and sex-matched healthy controls. Occipital cortex and whole brain analysis comparing all optic neuritis patients and controls revealed a selective decrease of MTR bilaterally in the visual cortex in patients [Brodmann area (BA) 17]. Whole brain analysis of patients fulfilling the McDonald criteria for multiple sclerosis (n = 20) showed a lower MTR compared to controls bilaterally in the visual cortex (BA 17/18), left hippocampus, bilateral superior temporal gyrus, bilateral lenticular nuclei and the right cerebellum. There was no significant difference in the percentage of grey matter between patients and controls in the regions of abnormal MTR detected in the visual cortex. The intrinsic MTR decrease seen in patients suggests that there are structural changes in the visual cortex following an attack of optic neuritis. Potential mechanisms for this include trans-synaptic neuronal degeneration and cortical synaptic morphological changes; such abnormalities may also contribute to MTR abnormalities observed in the normal appearing grey matter in multiple sclerosis.